1993
DOI: 10.1126/science.8093417
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy of Inhibitory Interneurons in a Model of Temporal Lobe Epilepsy

Abstract: In humans temporal lobe epilepsy (TLE) is characterized by recurrent seizures, neuronal hyperexcitability, and selective loss of certain neuronal populations in the hippocampus. Animal models of the condition indicate that a diminution of inhibition mediated by gamma-aminobutyric acid (GABA) accounts for the altered function, and it has been hypothesized that the diminution arises because GABAergic basket interneurons are "dormant" as a result of their being disconnected from excitatory inputs. In hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(92 citation statements)
references
References 42 publications
7
83
1
1
Order By: Relevance
“…Such a mechanism has been reported in the hippocampus and EC layers II/III (Bekenstein and Lothman, 1993;Williams et al, 1993;Sloviter, 1987;Doherty and Dingledine, 2001;Sloviter et al, 2003;Kumar and Buckmaster, 2006). Experiments performed in pilocarpine-treated rats have also demonstrated that pharmacologically isolated, GABA A receptor-mediated IPSPs have more positive reversal potentials in neurons recorded in vitro from the epileptic subiculum, peirhinal cortex and amygdala (de Guzman et al, 2006;Benini and Avoli, 2005;Benini et al, 2011); these data often correlated with reduced levels of mRNA expression and immunoreactivity of the neuron-specific cotransporter KCC2.…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 65%
“…Such a mechanism has been reported in the hippocampus and EC layers II/III (Bekenstein and Lothman, 1993;Williams et al, 1993;Sloviter, 1987;Doherty and Dingledine, 2001;Sloviter et al, 2003;Kumar and Buckmaster, 2006). Experiments performed in pilocarpine-treated rats have also demonstrated that pharmacologically isolated, GABA A receptor-mediated IPSPs have more positive reversal potentials in neurons recorded in vitro from the epileptic subiculum, peirhinal cortex and amygdala (de Guzman et al, 2006;Benini and Avoli, 2005;Benini et al, 2011); these data often correlated with reduced levels of mRNA expression and immunoreactivity of the neuron-specific cotransporter KCC2.…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 65%
“…However, anticonvulsant drugs such as benzodiazepines (Schinkel, et al, 1996) and carbamazepines (Owen, et al, 2001) are not transported by the multidrug transporter P-glycoprotein, thus indicating that the second theory of drug resistance could hold valid for explaining pharmacoresistance of benzodiazepines upon prolonged SE. In regards to the development of pharmacoresistance to anticonvulsant therapy with SE, several mechanisms in favor of this second theory have been proposed recently which and include changes in GABA A receptor properties or subunit composition Macdonald, 1997, Macdonald andKapur, 1999), loss of GABAergic interneurons Esclapez, 1996, Obenaus, et al, 1993), changes in receptor-mediated regulation of GABAergic transmission (Bausch andChavkin, 1997, Mangan andLothman, 1996), and loss of excitatory synaptic input onto GABAergic interneurons (Bekenstein andLothman, 1993, Doherty andDingledine, 2001). Naylor et al (Naylor, et al, 2005) recently demonstrated in a hippocampal slice preparation obtained from pilocarpine induced SE rats a loss of postsynaptic GABA A receptor function which, in agreement with a previous study from our laboratory (Blair, et al, 2004), was the result of a marked increase in internalization of GABA A receptors subunits by 1-hr following SE-onset.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is also associated with increased excitability of principal hippocampal neurons [9][10][11][12][13], and pyramidal neurons in the aging hippocampus exhibit higher frequency bursting comprising sharp-wave-ripple complexes during large irregular activity [14]. When taken together, the above findings suggest that decreased number of GABA-ergic interneurons contributes to increased excitability of principal neurons in the aged hippocampus.…”
mentioning
confidence: 89%